กิจกรรมและเครือข่ายเศรษฐกิจชุมชน ตามปรัชญาเศรษฐกิจพอเพียง (SYSTEM AND COMMUNITY ECONOMIC NETWORK FOLLOWING THE SUFFICIENCY ECONOMY PHILOSOPHY) - บุญยะเสนา, พิมลพรรณ; หิมะกลัส, วรลักษณ์ (Srinakharinwirot Research and Development Journal of Humanities and Social Sciences, 2018)
This study was a part of a research that aimed to promote concrete implementation of sufficiency economy through participatory learning process of community groups. Moreover, this paper also developed and increased competency. The study was conducted in Ban Pong 3, Intakhin Sub-District, Mae Tang District, Chiang Mai Province by using participatory action research. The results indicated that Ban Pong 3 had physical capital, human capital social capital and environment capital which were main factors of sustainable development.Besides, the economic activities of different community groups were concordant with the progressive sufficiency economy that emphasized the sufficiency at group or organization level. According to the potential development and network promotion, there was a cooperation between community, local developers and researchers to define targets and establish networks of sufficiency economy in various aspects such as production, marketing of OTOP products and community financial institutions. Observation visit was held to practice analysis process and prepare the business plan to the researchers to further vocational training or community development project. After that, the business plan was determined for production trial and market testing in the community until achieving satisfactory results.Then, the products were distributed to other community networks. Regarding the primary test results, therefore, it was highly feasible to shift the sufficiency economy to the third level as the progressive sufficiency economy which focused on the sufficiency at network level.